Implementing Differentiated Learning Using the Problem-Based Learning Model to Stimulate Students' Problem-Solving Skills - Syarqia, Lu'lu'; Suyatna, Agus; Suana, Wayan (Universitas Syiah Kuala, 2024)
The lack of implementation of differentiated learning causes teachers to be unable to accommodate students' various learning styles, which in turn reduces students' problem-solving abilities. This research aims to determine the influence of implementing content and process differentiation learning using the PBL model on improving problem-solving skills for each learning style of students and to identify the problem-solving skills that may arise from differences in learning styles. The research design used was a one-group pretest-posttest design. The research sample consisted of students in classes X-1 and X-2 at Public Senior High School Bandar Lampung in the academic year 2023/2024. The data collection method is through tests using pretest and posttest questions with indicators of problem-solving ability, and data analysis using paired difference tests (paired sample t-test) and one way ANOVA. The results of the study indicated a difference between the pretest and posttest scores of the students, where the posttest scores were higher than the pretest scores, indicating an improvement in students' problem-solving skills. The N-gain value was greater than 0.05, indicating no difference in problem-solving skills.